Rural Household’s Utilization of the Indigenous Vegetables - Israel, Perlita (International Journal of Arts, Sciences and Education, 2023)
The indigenous vegetables (IV) are nature’s copious blessings to the rural community. These vegetables can thrive and remain productive under varying climatic conditions. The rural community recognizes the value of IV, not only for human consumption, but for other valuable purposes as well. The aim of this study is to explore the rural household utilization of IV. The descriptive survey method, using validated structured interview, was employed to gather data from the randomly selected 60 respondents from the rural barangays of Municipality of Ibajay, Aklan, Philippines from January to September 2021. The interview results revealed that pako-pako (Diplazuim esculetum) was the most frequently consumed vegetable in the rural households. The vegetables were oftentimes harvested near the riverbanks, and were available throughout the season of the year. The leaves and stalks of the vegetables were recurrently consumed as food except for nipa (nypa fruiticans), in which only the core part is used as food. The results further disclosed that 28 or 46.47% of the respondents consumed IV in their households 16-20 times a month. The vegetables soup with fish or meat (tinuea) and vegetables in coconut milk (linabug)were the common dishes prepared from IV. Aside from the culinary uses, the rural household also utilized indigenous vegetables as feed for animals and for traditional medicinal purposes. Moreover, the IV were found beneficial to the households, especially during times of disaster and calamities, where food is scarce, especially during Covid 19 pandemic. Further studies are needed to establish the biochemical components of indigenous vegetables. Value adding the indigenous vegetables through product development was also suggested.